Copolymers of bipyridinium and metal (Zn & Ni) porphyrin derivatives; theoretical insights and electrochemical activity towards CO2. Issue 32 (2nd June 2021) - Kochrekar, Sachin; Kalekar, Ajit; Mehta, Shweta; Damlin, Pia; Salomäki, Mikko; Granroth, Sari; Meltola, Niko; Joshi, Kavita; Kvarnström, Carita
Abstract : Electropolymerization of keto functionalized porphyrins and 4, 4′-bipyridine. Abstract : This study reports the electropolymerization of novel keto functionalized octaethyl metal porphyrins (Zn 2+ and Ni 2+ ) in the presence of 4, 4′-bipyridine (4, 4′-bpy) as a bridging nucleophile. The polymer films were characterized by electrochemical, spectroscopic (UV-Vis, XPS, FT-IR and Raman spectroscopy) and imaging (AFM and SEM) techniques. The absorption and electronic spectra confirm the presence of both porphyrin and 4, 4′-bipyridine units in the film. The surface morphology reveals homogeneous film deposition with average roughness values of approx. 8 nm. The theoretical studies performed offered insights into the interplay of different metal centres (Zn 2+ and Ni 2+ ) and the keto functionality of the porphyrin unit in the formation of copolymer films. The electrochemical interaction of polymer films with CO2 suggests a reversible trap and release of CO2 with low energy barriers for both the polymers.